Towards a Theory of Collaborative Learning at Adult Learning Events: A Grounded Study - Julia Storberg-Walker; Colleen Aalsburg Wiessner (Adult Education Research Conference, 2007)
This roundtable focuses on the work-in-progress of building grounded theory. Specifically, the researchers will describe the context, the research project, and the iterative, collaborative theory building developments that have been in process over the past 27 months. Critique is sought from a variety of perspectives, including feminist, critical race, and other theories.